CORPUS-BASED LEXICAL BUNDLES IN AMERICAN PRESIDENTIAL INAUGURAL SPEECHES - Ayadi, Mouna (Sanata Dharma University, Yogyakarta, 2025)
The aim of this paper was to investigate the use of lexical bundles in the inaugural speeches of Democratic and Republican presidents in the United States in order to identify linguistic differences associated with lexical bundles. Drawing on Biber et al. (2004) framework, the study used AntConc software (version 3.5.9; Anthony, 2020) to analyse the lexical bundles used in the speeches. The study found that noun phrase (NP) fragments were the common structural pattern in all speeches. Democratic presidents tended to use NP + of phrase fragments, whereas Republican presidents used prepositional phrase (PP) + of fragments. In terms of the functional classification, both political parties showed a strong priority for referential expressions. These findings point to different linguistic styles associated with each political party, influencing their communication styles in public discourse. Future research is encouraged to look into how linguistic patterns influence political communication and persuasive strategies.